OP03 Anti-SARS-CoV2 antibody responses are attenuated in patients with Inflammatory Bowel Disease treated with infliximab. (27th May 2021) - Kennedy, N A; Goodhand, J; Bewshea, C; Nice, R; Chee, D; Lin, S; Chanchlani, N; Butterworth, J; Cooney, R; Croft, N; Hart, A; Irving, P; et al.
Abstract: Background: Anti-TNF drugs increase the risk of serious respiratory infections and impair protective immunity following pneumococcal, influenza, and viral hepatitis vaccinations. Therefore, we sought to determine whether patients with inflammatory bowel disease treated with infliximab have attenuated serological responses following SARS-CoV-2 infection. Methods: CLARITY IBD is a multicentre, prospective observational cohort study. Antibody responses in participants treated with infliximab were compared to a reference cohort treated with vedolizumab, a gut-selective anti-integrin α4β7 monoclonal antibody that is not associated with impaired vaccine responses or increased susceptibility to systemic infections. 6935 patients were recruited from 92 UK hospitals between 22 nd September and 23 rd December 2020. Nucleocapsid anti-SARS-CoV2 antibodies were measured using the Roche Elecsys assay. Clinical data and serum were collected every 8 weeks. Durability was defined as nonreduction in antibody level by at least 50% from baseline. Results: At baseline, rates of symptomatic and proven SARS-CoV-2 infection were similar between groups. Seroprevalence was lower in infliximab- than vedolizumab-treated patients (3.4% [161/ 4685 ], vs 6.0% [134/ 2250 ], p<0.0001). Multivariable logistic regression analyses confirmed that infliximab (vs vedolizumab; odds ratio [OR] 0.66 [95% CI 0.51–0. 87 ], p=0.0027) and immunomodulator use (OR 0.70 [95% CI 0.53–0. 92 ], p=0.012) were independently associated with lower seropositivity (Fig 1). In patients with confirmed SARS-CoV-2 infection seroconversion was observed in fewer infliximab- than vedolizumab-treated patients (48% [39/ 81 ], vs 83% [30/ 36 ], p=0.00044) and the magnitude of anti-SARS-CoV2 reactivity was lower (median 0.8 cut off index (COI) [0.2–5. 6 ] vs 37.0 [15.2–76. 1 ], p<0.0001). An initial increase in anti-SARS-Cov2 antibody reactivity was observed four weeks after a positive PCR test, in vedolizumab-(47.2 COI [IQR 24.1 - 113. 0 ] vs 14.5 COI [IQR 0.4 – 30. 7 ], p=0.0079), but not infliximab-treated patients (0.7 COI [IQR 0.2 - 7. 5 ] vs 1.1 COI [IQR 0.4 - 4. 5 ], p=0.70) (Fig 2). Antibody responses after an initial positive reading were also less durable in infliximab-treated patients (hazard ratio 5.15 [95%CI 2.95–9. 00 ]; Fig 3), but durability was not influenced by immunomodulator use. Conclusion: Seroprevalence, seroconversion in PCR-confirmed cases, and the magnitude and durability of anti-SARS-CoV2 antibodies were reduced in infliximab- compared with vedolizumab-treated patients. Serological testing and virus surveillance should be considered in patients treated with anti-TNF drugs to detect suboptimal vaccine responses, persistent infection, and viral evolution to inform public health policy.